The role of pre-disinfection measures in reducing the microbial load of pig house facilities - V. O. Myronchuk; R. A. Peleno (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Premises for keeping animals and objects in them are constantly exposed to significant contamination with organic substances, substantially impacting the disinfection quality. To achieve its maximum effectiveness, it is essential to consistently perform pre-disinfection measures that create optimal conditions for the destruction of microorganisms. However, due to a lack of awareness, poor risk management, time and resource constraints, and lack of systematic controls, many livestock producers underestimate the importance of pre-disinfection measures, which include mechanical cleaning, detergent treatment, hydro-cleaning, and drying. Improper implementation or complete absence of pre-disinfection measures can create favorable conditions for the development of pathogenic microorganisms, which threatens the health and productivity of animals. The work aimed to establish the effect of pre-disinfection measures on the microbial load of piggery facilities. As a result of the conducted research, it was established that before the pre-disinfection measures were carried out at the facilities of pig farms, the total number of microorganisms in honey was from 5.12 ± 0.49 to 6.83 ± 0.54 log CFU/cm3 of washing. The least covered with microflora were feeding troughs, 5.5 % more feeders, 17 % walls, 19 % intercellular partitions, and 25.1 % floors. Carrying out mechanical cleaning of the researched objects of animal husbandry premises ensured a reduction of microflora on their surface from 1.6 to 8.1 % and treatment with the “Grass” agent – from 15.3 to 18.5 %. A decrease in the amount of microflora from 23.7 to 30.9 % on the floor, inter-cage partitions, walls, feeders, and drinking troughs was established after their hydro-cleaning with the high-pressure device “Aqua Master”, and the specified differences were probable (P < 0.05). It has been proven that the proper implementation of all stages of pre-disinfection requirements leads to a possible (P < 0.05) decrease in the microbial load, which was 28.7 % on the floor, 38.3 % on the intercellular partitions, 36.1 % on the walls, 32.0 % in the feeders, 8 %, and 34 % on water supply.